Direct speed finite control set model predictive control for PMSM drive – robustness analysis - Lisiński, Hubert; Tarczewski, Tomasz (Bulletin of the Polish Academy of Sciences Technical Sciences, 2025)
Currently, high-performance electrical drives with advanced control schemes are presented in the literature. Many of them will not be used in the industry because of implementation issues or difficulties in the optimal selection of control parameters. In this paper, two different model predictive control (MPC) schemes are developed for PMSM drive and compared in experimental tests both in time and frequency domains. To provide high-performance operation of the drive, a complex cost function is constructed, and a metaheuristic optimization algorithm is utilized for the automatic selection of weighting factors. Developed control schemes were implemented in a microprocessor-based prototype drive and examined in terms of robustness for three different moments of inertia. Trajectory tracking ability for step and ramp reference angular velocity, as well as load torque compensation, have also been investigated. The study makes an important contribution as a reliable and robust model predictive control scheme for PMSM drive with potential for industrial applications.